Three new species of Loxosceles Heinecken & Lowe, 1832 (Araneae, Sicariidae) from Brazilian caves - Bertani, Rogério; Bichuette, Maria Elina; Cordeiro, Lívia Medeiros; Gallão, Jonas Eduardo (European Journal of Taxonomy, 2024)
Three new species of recluse spiders are described from Brazilian caves with both males and females. Loxosceles boqueirao Bertani & Gallão sp. nov. is found in the State of Bahia, in the Serra do Ramalho karst area, it belongs to the rufescens species group, and is closely related to L. cardosoi Bertani, von Schimonsky & Gallão, 2018 and L. carinhanha Bertani, von Schimonsky & Gallão, 2018 from the same karst area. Thus, there are now three species in the Serra do Ramalho karst area closely related, but noticeably distinct morphologically from other species of Loxosceles. Loxosceles planetaria Bertani & Gallão sp. nov. and L. bodoquena Bertani & Gallão sp. nov. are found in the State of Mato Grosso do Sul, in the Serra da Bodoquena karst area. They belong to the gaucho species group and are closely related to L. gaucho Gertsch, 1967. These are the first species of Loxosceles described from this karst area in the State of Mato Grosso do Sul. Loxosceles boqueirao sp. nov. and L. bodoquena sp. nov. bear some troglomorphisms and are, herein, proposed as troglobitic species, whereas L. planetaria sp. nov. is proposed as a troglophilic species. Brazil has now 22 described species of Loxosceles.